2022
DOI: 10.1017/inp.2022.11
|View full text |Cite
|
Sign up to set email alerts
|

Prescribed burning followed by indaziflam enhances downy brome (Bromus tectorum) control

Abstract: B. tectorum (Bromus tectorum L.) is a highly invasive winter annual grass that can fill open niches in native plant communities. Prescribed burning is often used to control B. tectorum and can be combined with herbicide treatments to extend the duration of control and promote the native plant community. Several herbicides have been evaluated in conjunction with burning for B. tectorum control, although the herbicide indaziflam has not. In September 2017, two B. tectorum infested sites were burned in Colorado f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Land managers should be aware that short-term treatment outcomes may be inconsistent, and control may improve over time when using indaziflam alone, as was observed in our study. Seedorf et al (2022) observed more consistent short-term (1 to 2 YAT) B. tectorum control when tank mixing indaziflam with imazapic compared with applying indaziflam on its own, and imazapic consistently reduced B. tectorum abundance at 9 MAT in our study (Figures 1A and B and 2A and B). Coupled with its selectivity against annual grasses at low use rates (Kyser et al 2013), the short-term effectiveness of imazapic may make it a suitable tank-mix partner for indaziflam that can provide reliable short-term B. tectorum control.…”
Section: Perennial Grass Coversupporting
confidence: 74%
See 2 more Smart Citations
“…Land managers should be aware that short-term treatment outcomes may be inconsistent, and control may improve over time when using indaziflam alone, as was observed in our study. Seedorf et al (2022) observed more consistent short-term (1 to 2 YAT) B. tectorum control when tank mixing indaziflam with imazapic compared with applying indaziflam on its own, and imazapic consistently reduced B. tectorum abundance at 9 MAT in our study (Figures 1A and B and 2A and B). Coupled with its selectivity against annual grasses at low use rates (Kyser et al 2013), the short-term effectiveness of imazapic may make it a suitable tank-mix partner for indaziflam that can provide reliable short-term B. tectorum control.…”
Section: Perennial Grass Coversupporting
confidence: 74%
“…At Site 1, the wildfire that occurred in August 2019 likely precluded our ability to detect treatment effects on perennial grass cover at 45 and 57 MAT. Our findings add to a growing number of studies demonstrating that indaziflam can selectively control annual grasses with minimal risk to established perennial plants (Clark et al 2019(Clark et al , 2020Fowers and Mealor 2020;Hart and Mealor 2021;Sebastian et al 2016Sebastian et al , 2017aSeedorf et al 2022), but future research should evaluate the potential for longer-term impacts to native perennials with repeated treatments. Impacts to P. spicata and A. tridentata seedlings have been observed in a grow room study (Clenet et al 2019), and grazing managers have long understood the importance of allowing perennial grasses to complete their reproductive cycles in at least some years (Burkhardt and Sanders 2012), which suggests that the potential for longer-term impacts from repeated indaziflam treatments may be different.…”
Section: Perennial Grass Covermentioning
confidence: 58%
See 1 more Smart Citation
“…A posttreatment statistical analysis was not performed for the mulched (LMU21) location due to lack of variation when all treated stems have 100% defoliation. The arcsine square-root transformation was used to normalize variance for old-growth (CX36) location percent defoliation with modifications suggested by Seedorf et al (2022) for treatments with complete defoliation. The ANOVA was performed by evaluation date and excluded treatments with 100% defoliation to accurately estimate the random block and residual error effects.…”
Section: Methodsmentioning
confidence: 99%
“…Most available research on the interaction between fire and herbicide use is focused on timing prescribed fire to interact favorably with spray regimens (Simmons et al 2007; Calo et al 2012; Emery et al 2013). This includes recent work in a Colorado Foothills Shrubland showing that native plant diversity increased more in plots where indaziflam was applied after fall prescribed fire versus plots without fire (Seedorf et al 2022). Conversely, there is currently no information describing how pre-wildfire management with indaziflam shapes community assembly processes post-fire.…”
Section: Introductionmentioning
confidence: 99%